Productive integration, economic recession and employment in Europe: an assessment based on vertically integrated sectors - Davide Villani; Marta Fana (European Commission, Joint Research Centre (JRC), 2020)
The Covid-19 crisis has revamped the discussion about the redefinition of GVC. This paper contributes to the debate, analysing the productive relationships between European countries in four key manufacturing activities. In particular, the paper addresses two objectives. First, it maps the degree of productive integration in Europe, focusing on the generation of employment in the production of exported intermediate inputs and final goods. Second, it provides a preliminary assessment of the potential impact on employment that the current economic crisis will have on some manufacturing activities across Europe. The analysis is realised employing the concept of vertically integrated labour (Pasinetti, 1973) which allows to account for the employment directly and indirectly involved in the production of final goods. The estimations are derived from Multi-Regional Input-Output tables to map the supply chain and to differentiate between the employment involved in the production of exported intermediate inputs and final goods. The results show that most of the employment involved in the production of final output of the activities studied in the paper is linked to international trade. Although Europe shows a high degree of productive links, there are important differences in the modality of insertion in the productive structure of European countries. Moreover, the impact on the level of employment due to the current economic crisis can be significant, affecting more than 1.3 million of people in Europe. These results are relevant to policy makers, who should consider carefully the high degree of linkages of the European economies when designing measure of support to the economy as domestic uncoordinated policies may have a reduced impact given the existing productive structure.
Keywords: 330; Vertically integrated labour; Covid-19; Global value chains; Productive integration